2019
DOI: 10.1016/j.bpj.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Bacteria by γ-Irradiation to Investigate the Interaction with Antimicrobial Peptides

Abstract: The activity of antimicrobial peptides (AMPs) has been investigated extensively using model membranes composed of phospholipids or lipopolysaccharides in aqueous environments. However, from a biophysical perspective, there is a large scientific interest regarding the direct interaction of membrane-active peptides with whole bacteria. Working with living bacteria limits the usability of experimental setups and the interpretation of the resulting data because of safety risks and the overlap of active and passive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 79 publications
2
10
0
Order By: Relevance
“…Fluorescence spectroscopy using labeled peptides is used to determine the binding stoichiometry and binding constant of peptides to cells. Studies reported for TBKKG6A labeled with nitrobenzodiazole show that this peptide binds to E. coli cells in a 1 × 10 6 :1 (peptide:cell) stoichiometry; similar values are reported in the literature for other peptides ( 29 31 ). The binding constant of TBKKG6A to cells, expressed as a dissociation constant, reveals a very tight binding.…”
Section: Binding Studiessupporting
confidence: 84%
See 2 more Smart Citations
“…Fluorescence spectroscopy using labeled peptides is used to determine the binding stoichiometry and binding constant of peptides to cells. Studies reported for TBKKG6A labeled with nitrobenzodiazole show that this peptide binds to E. coli cells in a 1 × 10 6 :1 (peptide:cell) stoichiometry; similar values are reported in the literature for other peptides ( 29 31 ). The binding constant of TBKKG6A to cells, expressed as a dissociation constant, reveals a very tight binding.…”
Section: Binding Studiessupporting
confidence: 84%
“…Solid state 31 P NMR is used to examine the interaction of peptides with the phospholipids of live bacteria. As the number of phosphate groups in a bacterial membrane is estimated to overwhelm that found in bacterial RNA, 31 P is a suitable probe of membrane dynamics. The first paper on this topic dates back to 2000 and reports on the interactions of caerin 1.1, caerin 4.1, and maculatin 1.1 with the Gram-positive bacteria B. cereus and S. epidermidis.…”
Section: Binding Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed an interesting, varied mosaic of statistically significant differences in the regulation of some of the key genes involved in immune modulation. This variability can be justified by the strain-dependent response to inactivation methods among LAB, as for bacteria in general, documented in previous studies, especially on radiation resistance ( 28 ), structure composition ( 31 ), immune stimulation ( 25 ), and adhesion abilities ( 23 ), just to name a few. For example, IFNα, mostly involved in antiviral activity ( 44 ), was downregulated by heat-killed Lc.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to inactivated bacteria which is defined as “metabolically-active non-replicative,” potentially preserving all (or most of) the characteristics of the live bacterium while guaranteeing a high level of safety. Evidence showed that gamma irradiation successfully protected surface antigens and cell composition of bacteria compared to other means of inactivation (e.g., heat treatment) ( 31 ). Despite the great potential of this technology, few studies in the literature explored the application of gamma irradiation to generate paraprobiotics.…”
Section: Introductionmentioning
confidence: 99%